Improved impact responses of a honeycomb sandwich panel structure with internal resonators. Issue 5 (3rd May 2020) - Li, Q. Q.; He, Z. C.; Li, E.; Cheng, A. G.
ABSTRACT: In this article, a decahedral honeycomb sandwich panel structure with periodic internal resonators is developed to effectively mitigate the impact force and dissipate the impact energy. Five types of local-resonance microstructure with the property of negative effective mass are applied on the sandwich structure to study the effects of different resonators on load attenuation. The theoretical and numerical results show that the multi-resonator model (MM) exhibits the best attenuation effect. The damping characteristic is added to the MM to further improve the structure responses. The analytical results clearly demonstrate that the combination of damping characteristic and local resonance of multi-resonators can significantly dissipate the impact energy and mitigate the dynamic load. Optimization analyses are also carried out to optimize the spring stiffness, lumped mass and damping coefficient. The performance of the sandwich panel structure is significantly improved with a relatively small structural mass.